Developing STEM Literacy through Interdisciplinary Learning on Environmental Change - Dida Firgiawan; Ari Widodo; Riandi Riandi; Sri Angraeni (Unnes Science Education Journal, 2026)
This study aimed to develop and evaluate an interdisciplinary STEM learning model integrated with Education for Sustainable Development to enhance senior high school students’ STEM literacy on environmental change topics. A mixed-methods approach with a quasi-experimental pretest–posttest control group design was employed, supported by qualitative analysis of students’ learning processes. Quantitative data were collected using a validated 24-item test measuring four dimensions of STEM literacy science, technology, engineering, and mathematics and analyzed using comparative statistics and normalized gain. Qualitative data were analyzed thematically to examine students’ systemic understanding. The results showed that the experimental group achieved higher improvement (mean pretest = 60.88; posttest = 93.39; normalized gain = 0.86, high) compared to the control group (mean pretest = 59.02; posttest = 85.87; normalized gain = 0.69, moderate). Across the four STEM literacy dimensions, the experimental group reached the high category on science (0.86), technology (0.89), engineering (0.81), and mathematics (0.75), whereas the control group reached the high category only on engineering (0.74) and remained in the moderate category on science (0.57), technology (0.68), and mathematics (0.59). It can be concluded that integrating Education for Sustainable Development into interdisciplinary STEM learning effectively enhances students’ holistic STEM literacy and supports sustainability-oriented science learning.